Incidence and predictors of violence from clients, intimate partners and police in a prospective US-based cohort of women in sex work. (3rd November 2020) - Decker, Michele; Rouhani, Saba; Park, Ju Nyeong; Galai, Noya; Footer, Katherine; White, Rebecca; Allen, Sean; Sherman, Susan
Abstract : Objective: Gender-based violence threatens women's health and safety. Female sex workers (FSWs) experience violence disproportionately, yet prospective data on violence predictors is lacking. In the first US-based prospective FSW cohort study, we examine incidence rates (IRs) and predictors of violence from distinct perpetrators: paying clients, non-paying intimate partners and police. Methods: The parent cohort (Sex Workers and Police Promoting Health In Risky Environments) recruited street-based cisgender FSWs in urban Baltimore, MD (n=250) with 5 assessments at 3-month intervals through 12-month follow-up. Stratifying by violence perpetrator, we characterise violence at baseline, IR over the study period and time-varying predictors using Poisson models. Results: The violence IR per person year was highest for client-perpetrated violence (0.78), followed by intimate partner violence (IPV; IR 0.39), and police violence (IR 0.25). Prevalence over the 12-month follow-up period among participants with complete visit data (n=103), was 42% for client violence, 22% for IPV and 16% for police violence. In adjusted analyses, risk factors for incident violence varied across perpetrators and included entry to sex work through force or coercion (adjusted IR ratio (aIRR)IPV 2.0; 95% CI 1.2 to 3.6), homelessness (aIRRIPV 2.0; 95% CI 1.3 to 2.9; aIRRpolice 2.7; 95% CI 1.3 to 5.8) and daily injection drug use (aIRRclient 1.9; 95% CI 1.2 to 3.0). Risk of incident client violence and IPV was elevated by past abuse from each respective perpetrator. Help-seeking following abuse was limited. Conclusions: FSWs face profound, enduring risk for violence from a range of perpetrators, likely enabled by criminalisation-related barriers to justice and perpetrator impunity. FSWs represent a priority population for access to justice, trauma-informed healthcare and violence-related support services. Structural vulnerabilities including homelessness and addiction represent actionable priorities for improving safety and health.